Religious Conversion in Marginalized Communities in the Perspective of Islamic Education Values - Abdul Rahim; Fariha Inayati (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2023)
The diversity of religions in the world produces a unique phenomenon, namely religious conversion or conversion of religious adherents from one religion to another, for example converting from Christianity to Hinduism, Hinduism to Islam, and so on. The phenomenon of religious conversion, as experienced by parents in Kaliagung Hamlet, Kendalrejo Village, Tegaldlimo, Banyuwangi is because parents who experience religious conversion from Hinduism have different experiences and backgrounds before they decide to embrace Islam. This is closely related to human psychological problems because these actors experience drastic changes in their lives. Likewise with the way parents who practice religious conversion in instilling the values of Islamic education in their children. Because Islamic religious education has a very important role and position in the life of religious people. Based on this phenomenon, the authors are interested in studying Religious Conversion in Kaliagung Hamlet, Kendalrejo Village, Tegaldlimo, Banyuwangi. The research focus in this study is 1) What are the factors behind the occurrence of religious conversion? 2) How are the perpetrators of religious conversion in instilling the values of Islamic education in children? This research uses a descriptive qualitative approach. Methods of data collection using observation, interviews, and documentation. While the technique of obtaining data using purposive sampling. Furthermore, for data analysis, the authors used a qualitative descriptive analysis technique, namely data in the form of written and oral data from the informants studied to fully describe the phenomena that exist in the field. Based on the analysis that the researchers found in the field regarding the conversion of parents' religion and the inculcation of Islamic religious education values in children, the conclusion is that the factors behind parents experiencing a religious conversion in Kaliagung Hamlet, Kendalrejo Village, Tegaldlimo, Banyuwangi originate from internal factors (from within) and internal factors. external (from outside/environment). The values of Islamic religious education are: instilling faith and worship in children. The values of aqidah are faith in Allah, faith in angels, faith in Allah's books, faith in Allah's messengers, faith in the Last Day, and faith in qada' and qadar. While the values of worship are teaching the Qur'an, prayer, zakat, fasting, and pilgrimage. Whereas way parents practice religious conversion by instilling the values of Islamic education by motivating children, setting an example for children, and forming habits in children.